MANAJEMEN KRISIS DINAS KESEHATAN PONOROGO DALAM MENGHADAPI COVID-19 VARIAN BARU OMICRON - Bambang Setyo Utomo; Alfianandra Wafiq Pradana; Fandi Avista Baihaqi; Mohamad Abiyyu Althof; Agung Wicaksono; Fahmi Ziaulhaq (Jurnal Komunikasi dan Budaya, 2022)
The emergence of a new covid-19 variant (Omicron) has had a real impact in Ponorogo. In an effort to overcome the crisis that occurs, it is necessary to pay special attention and handling to the authorities or the community. The health Office as an institution that is at the forefront in responding to health issues must act quickly before the issue develops into a continuing crisis phenomenon. One of the phenomena of the communication crisis in this pandemic era is the emergence of an excessive concern about the impact of the spread of disease and also the policies made by authorized institutions. Referring to the theory expressed by W. Thompson regarding the 4R (Readiness, Radar, Response, Recovery) in responding to a crisis. The purpose of this study was to determine the crisis management strategy of the Ponorogo Health Service in dealing with the issue of the Omicron Variant Covid-19 crisis. This research is qualitative research with descriptive method. Various data collection processes are carried out both primary and secondary, such as: conducting in-depth interviews with the head of the P2P Health Office, taking documentation of the level of affected patients in Ponorogo. The results of this study indicate that the crisis management carried out by the Ponorogo Health Service in dealing with the new variant of Omicron is in accordance with Thompson's 4R theory stage.